Advances in parasitic plant research: proceedings, 6th Parasitic Weeds Symposium, 16-18 April 1996, Junta de Andalucia, Direccion General de Investigacion Agraria, Cordoba, Spain - Moreno, M.T.; Cubero, J.I.; Berner, D.K.; Joel, D.; Musselma, L.; Parker, C. (1996)
This 6th symposium on parasitic plants was held in Spain in 1996 during which 101 papers were read, divided into 6 headings, including evolution and population structure, form, structure, biochemistry and physiology of the parasitic plant. The relationship between parasite and host, including methods of germination, host ranges and ecology, resistance mechanisms, selection methods to resistance of host plants, control methods covering the fields of conventional, integrated and biocontrol methods were discussed. The parasitic plants dealt with here included Orobanche spp., Striga spp., Cuscuta reflexa, Amyema mackayense, Viscum album, Ramphicarpa fistulosa and Santalum album.